Common processes and different trayectories around the lands of indians villages of Jujuy. Between the XVII and XIX centuries - Sica, Gabriela (Revista del Museo de Antropología, 2016)
This paper analyzes the history of the Indian villages of Jujuy and their communal lands from the final pacification of its territory in the late sixteenth century to the early decades of the nineteenth century. In this long history there are some common processes and regional differences conditioned by location, demography, access to resources and relationships with the “encomenderos”. They highlight the political capacity of ethnic authorities to negotiate in common processes, recourse to justice or under the authorities in military or political situations that could be favorable. The decline and extinction of several of these “pueblos de indios” will occur in the last decades of the eighteenth century and the first decades of the nineteenth century by the advance of private property and the new liberal ideas.